Interfaith Dialogue and the Golden Age of Christian-Jewish Relations - Ariel, Yaakov (Studies in Christian-Jewish Relations, 2011)
Since the 1960s, remarkable changes have taken place in the relationship between the Christian and Jewish communities in the West. A movement of interfaith dialogue stood at the center of the developments, serving as a catalyst that helped to bring about reconciliation and improvement in the attitudes of Christians towards Jews. Beginning in the English-speaking world at the turn of the twentieth century, the dialogue between Jews and non-Jews gained more ground in the decades between the two world wars. The movement of interfaith reconciliation advanced considerably in the years after World War II and reached a "golden age" in the late 1960s and 1970s, when an unprecedented momentum for reconciliation and dialogue between the faiths flourished in Europe, America, Israel, and other countries. Despite occasional set-backs and while involving mostly members of liberal or mainstream groups, this movement helped to improve the relationship between Christians and Jews in an unprecedented manner and on a worldwide scale.